PENGARUH ENDORSER ULAMA TERHADAP SIKAP DAN MINAT BELI KONSUMEN - Muchsin Muthohar; Amin Ramadhan Triatmaja (Jurnal Bisnis dan Ekonomi, 2013)
The purpose of this research is to explain the influence of Islamic preacher toward attitude and consumers’ purchase intention as well as to find out of what dominant factor that influence consumer attitude and consumers purchase intention. Primary data were collected from 300 respondents using area random accidental sampling from kabupaten Sleman, kabupaten Bantul dan Kota Yogyakarta. Research findings show that all characteristics of Islamic preacher endorser as an independent variables (physical attractiveness, credibility source, congruency and trustworthiness) being observed partially and simultaneously significantly influence toward consumer attitude and consumers purchase intention. There is an interesting finding in this research that consumers purchase intention is more influenced by product benefit than Islamic preacher as an endorser. This finding indicates those respondents are rationale consumers. Key words: islamic preacher endorser, consumers attitude, consumers purchse intention